Dating Practices: A Moral Negotiation in Pesantren - Basri, Basri; Nasir, Mohd.; Fiqiyah, Maskanatul; Rizal, Syamsul; Zainuddin, Zainuddin (SCAD Independent, 2024)
The main aim of this article was to see the public space of Pesantren as an arena for negotiating Islamic moral ideas and modernity. The practice of dating in Islamic literature is linked to immoral action because it is contrary to Islamic teachings that prohibit relationships outside marriage. It has become an important part of Islamic moral education. Dating in Pesantren is prohibited, and it is a relationship outside marriage. However, there are still many students who develop romantic relationships with members of the opposite sex in the public spaces of Pesantren. Through ethnographic studies, researchers observed Santriwati’s dating practices and interviewed them to determine the moral basis for these actions. Based on these observations at the Pesantren Madrasah Ulumul Qur’an (MUQ) Langsa, the practice of dating was carried out by santriwati by hiding behind buildings and rooms in the Islamic boarding school. This secretive and tactical action was carried out not to confront the rules made by the ustadz but as part of a negotiation between obeying the rules and the choice to continue dating. The researcher concluded that, even though the Islamic boarding school public space is filled with moral values produced by kyai and ustadz, the students still can carry out actions outside the Islamic boarding school's ideas of morality.